Sulphide signalling potentiates apoptosis through the up‐regulation of IP3 receptor types 1 and 2. (7th May 2013) - Lencesova, L.; Hudecova, S.; Csaderova, L.; Markova, J.; Soltysova, A.; Pastorek, M.; Sedlak, J.; Wood, M. E.; Whiteman, M.; Ondrias, K.; Krizanova, O.
Abstract Aim To investigate an interaction between the calcium and sulphide signalling pathways, particularly effects of the slow H2S release donor morpholin‐4‐ium‐4‐methoxyphenyl‐(morpholino)‐phosphinodithioate (GYY4137) on the expression of inositol 1, 4, 5‐trisphosphate receptors (IP3R) with the possible impact on the apoptosis induction in HeLa cells. Methods Gene expression, Western blot analysis, apoptosis determination by Annexin‐V‐FLUOS and drop in mitochondrial membrane potential by 5, 5′, 6, 6′‐tetrachloro‐1, 1′, 3, 3′‐tetraethylbenzimidazolyl‐carbocyanine iodide (JC1) and immunofluorescence were used to determine differences in control and GYY4137‐treated HeLa cells. Results In HeLa cell line, GYY4137 (10 μm) up‐regulated expression of the IP3R1 and IP3R2, but not IP3R3 on both mRNA and protein levels. Concurrently, cytosolic calcium increased and reticular calcium was depleted in concentration‐dependent manner, partially by the involvement of IP3R. Depletion of calcium from reticulum was accompanied by increase in endoplasmic reticulum (ER) stress markers, such as X‐box, CHOP and ATF4, thus pointing to the development of ER stress due to GYY4137 treatment. Also, GYY4137 treatment of HeLa cells increased the number of apoptotic cells. Conclusion These results suggest an involvement of H2S in both IP3‐induced calcium signalling and induction of apoptosis, possibly through the activation of ER stress.